2008
DOI: 10.1128/jb.00363-08
|View full text |Cite
|
Sign up to set email alerts
|

SO-LAAO, a Novell-Amino Acid Oxidase That EnablesStreptococcus oligofermentansTo OutcompeteStreptococcus mutansby Generating H2O2from Peptone

Abstract: We previously demonstrated that Streptococcus oligofermentans suppressed the growth of Streptococcus mutans, the primary cariogenic pathogen, by producing hydrogen peroxide (H 2 O 2 ) through lactate oxidase activity. In this study, we found that the lox mutant of S. oligofermentans regained the inhibition while growing on peptone-rich plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 42 publications
4
88
0
1
Order By: Relevance
“…For example, P. aeruginosa is reported to kill Candida in multi-species biofilms by using virulence factors which are well characterized in human infections [53][54]. Tong et al reported that Streptococcus oligofermentans uses L-amino acid oxidase to generate hydrogen peroxide (H 2 O 2 ) from peptone and suppress the growth of S. mutans in a peptone-rich multi-species biofilms [55]. Rao et al reported that marine bacterium Pseudoalteromonas tunicate produces antibacterial protein (AlpP) and inhibits the growth of other marine bacteria isolated from the same environment [56].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…For example, P. aeruginosa is reported to kill Candida in multi-species biofilms by using virulence factors which are well characterized in human infections [53][54]. Tong et al reported that Streptococcus oligofermentans uses L-amino acid oxidase to generate hydrogen peroxide (H 2 O 2 ) from peptone and suppress the growth of S. mutans in a peptone-rich multi-species biofilms [55]. Rao et al reported that marine bacterium Pseudoalteromonas tunicate produces antibacterial protein (AlpP) and inhibits the growth of other marine bacteria isolated from the same environment [56].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…Instead, HPr-Ser-P and three phosphoenolpyruvate-dependent sugar-phosphotransferase system (PTS) EII complexes, EIIAB Man , FruI, and EII Lev , assume primary control over the transport and catabolism of nonpreferred carbohydrates (1,46,47,49). The "mitis group" streptococci are major competitors of S. mutans; however, how their CCR is regulated is not well understood.Our previous studies have shown that Streptococcus oligofermentans, an oral commensal of the mitis group, can outcompete S. mutans by producing abundant H 2 O 2 when protein or glucose is present (37,38). Further, S. oligofermentans, although it utilizes fewer saccharides than S. mutans, metabolizes galactose more efficiently and yields greater cell mass on galactose than on glucose.…”
mentioning
confidence: 99%
“…Our previous studies have shown that Streptococcus oligofermentans, an oral commensal of the mitis group, can outcompete S. mutans by producing abundant H 2 O 2 when protein or glucose is present (37,38). Further, S. oligofermentans, although it utilizes fewer saccharides than S. mutans, metabolizes galactose more efficiently and yields greater cell mass on galactose than on glucose.…”
mentioning
confidence: 99%
“…It can produce H 2 O 2 as a means of excreting excessive oxygen and serves as a non-specific antimicrobial agent, which can inhibit S. mutans and other anaerobic periodontal pathogens growth. 73 However, it is obtrusive to say S. sanguinis is 100% benign due to its association with bacterial endocarditis. coaggregation between F. nucleatum and many Gram-positive bacterial species has been observed, those coaggregations are rarely inhibited by sugars.…”
mentioning
confidence: 99%